ILRI in Asia: an assessment of priorities for Asian livestock research and development - Vercoe, John; Coffey, S.; Farrell, D.J.; Rutherford, A.S.; Winter, W.H. (International Livestock Research Institute, 1997)
The purpose of this discussion paper is, firstly, to promote debate amongst potential clients of ILRI's research in South and South-East Asia on what ILRI could do in these regions, in collaboration with the NARS, which will assist the development of the livestock industries and, secondly, to provide advice to the ILRI Board and management on the rational for ILRI involvement in the regions, the nature of that involvement, and the mechanisms and process by which ILRI might maximise the benefits from its investment into research and development, particularly in these regions. The paper looks initially at the economic trends in selected countries in both regions and assesses the likely impact of this on dietary preferences and priorities. Having established the potential demands in the regions for the major livestock products (meat, milk, draft-power, eggs and, to a lesser extent, leather, wool and hair) in the next decade or so, the ways in which deficits in supply can be met from existing systems are assessed. The major constraints to improved production are identified and the role that technologically based research can play in alleviating these constraints is examined. The discussion paper then canvasses options for ILRI's participation, facilitation and leadership in some areas of priority research for the region and some possible mechanisms by which ILRI might achieve such objectives are detailed.